Blind quantum computation where a user only performs single-qubit gates. (October 2021) - Li, Qin; Liu, Chengdong; Peng, Yu; Yu, Fang; Zhang, Cai
Highlights: The model of blind quantum computation that users only do single-qubit gates is given. The specific blind quantum computation protocol in the given model is proposed. The proposed model is suitable in some experimental setups such as trapped ions. Abstract: Blind quantum computation (BQC) allows a user who has limited quantum ability to complete a quantum computational task with the aid of a remote quantum server, such that the user's input, output, and even the algorithm can be kept hidden from the server. Up to now, there are mainly two models of BQC. One is that the client just needs the ability to prepare single qubits initiated by Broadbent, Fitzsimons, and Kashefi and the other is that the client only needs to perform single-qubit measurements first given by Morimae. In this paper, we put forward a new model of BQC in which a user only requires implementing a few single-qubit gates. We also propose a specific BQC protocol where a user only needs to implement two kinds of single-qubit gates to show the feasibility of the presented model and thus answer positively the open question whether a verified BQC protocol that only requires single-qubit gates for the user can be designed. This circuit model is quite flexible since various users with the ability to perform different single-qubit gates may all have the chance to achieve BQC. Furthermore, compared with the other two models, it may be more suitable for practical implementation in some experimental setups such as trapped ions and superconducting systems since the single-qubit gates are the most exact operations in such systems.